Compact CPW-Fed Planar Monopole Antenna with Triple-Band Operation for WLAN/WiMAX Applications - Wang, Ping; Wen, Guang-Jun; Huang, Yongjun (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, we propose a compact coplanar waveguide (CPW) feed planar printed monopole antenna for WLAN/WiMAX applications. By employing two different types of structures-L-shaped slot and I-shaped notched slots, three distinct frequency bands with -10dB reflection coefficient, which correspond to 2.4GHz-2.6GHz, 3.4GHz-3.85GHz and the other at 4.9GHz-5.89GHz, can be achieved to covering 2.4/5.2/5.8 GHz WLAN and 2.5/3.4/5.5 WiMAX. Also, the antenna has a small size of 30mm×23mm, and can provide excellent property, including low profile, moderate gain, approximate omnidirectioal radiation pattern, which prove that the antenna is a good candidate for WLAN/WiMAX applications.